AI-DRIVEN POLITICAL DISINFORMATION AND PUBLIC TRUST OF INDONESIAN SOCIAL MEDIA USERS - R. Yogie Prawira (GoAcademica Research dan Publishing, 2025)
The development of Artificial Intelligence (AI) technology has transformed the landscape of political campaigns on social media through the massive production of disinformation, which is manipulative, and difficult to detect, such as deepfakes and automated text-based narratives. In Indonesia, this phenomenon poses a serious threat to democratic stability and digital polarization. This study aims to explore in depth how Indonesian social media users interpret, respond to, and experience the impact of exposure to AI-based political disinformation on their trust in the political system. This study aims to conceptually and critically analyze the mechanisms by which AI-based political disinformation degrades public trust in Indonesian social media users and to map existing regulatory gaps. This study employ, desk research or known as secondary research Secondary research is a method of gathering information and insights from various scientific literature, including reputable journal articles, digital research institute reports, and relevant policy documents in Indonesia. The study's findings indicate that AI-based political disinformation disables secondary cognitive verification systems through motivated reasoning mechanisms, which are then structurally amplified by filter bubble and echo chamber algorithms. This phenomenon gives rise to